Computing Reverse Degree Based Topological Indices of Vanadium Carbide. (7th February 2023) - Wei, Jianxin; Khalid, Asma; Ali, Parvez; Siddiqui, Muhammad Kamran; Nawaz, Asif; Hussain, Muzammil
Abstract: Graph theory has many applications in chemistry while studying the molecular structure of chemicals, moreover number of its applications are also increasing day by day. Applying Quantitative Structure-Activity Relationship (QSAR) methods has become a challenging task due to lack of data and knowledge of chemical compounds. The computation of topological indices is a well known topic in chemical graph theory. These indices are used to investigate and evaluate the basic structures and groupings of molecule in chemical substances. In this paper, we have attempted to figure out some topological indices which are based on degree and reverse degree of Vanadium Carbide.